The Analysis of Servant Leadership on Employee Performance through Knowledge Sharing at PT Pos Indonesia Kebonrojo Surabaya - Albilizar Rafly Hartana; Gendut Sukarno (Jurnal Ekonomi dan Bisnis Digital, 2023)
The aim of this research is to explore the influence of servant leadership and knowledge sharing on employee performance at PT Pos Indonesia Kebonrojo Surabaya. In this context, servant leadership refers to leaders who are oriented towards serving their employees and have the potential to create a positive work environment. Knowledge sharing is considered important in creating knowledge, innovation, and learning within the organization. The research used a questionnaire method to collect data from a population of 121 employees, with a sample size of 55 respondents obtained through the Slovin's formula. The data analysis employed the Partial Least Square (PLS) method. The findings indicate that servant leadership has a positive and significant influence on employee performance, as does knowledge sharing. Furthermore, servant leadership also has a positive and significant impact on knowledge sharing, and servant leadership positively and significantly influences employee performance through knowledge sharing. These findings highlight the interrelatedness among the three variables at PT Pos Indonesia Kebonrojo Surabaya